Lipid droplet dynamics in alcoholic fatty liver disease - Schulze, Ryan J. (Liver Res, 2019)
The rising incidence of alcohol-related liver disease (ALD) demands making urgent progress in understanding the fundamental molecular basis of alcohol-related hepatocellular damage. One of the key early events accompanying chronic alcohol usage is the accumulation of lipid droplets (LDs) in the hepatocellular cytoplasm. LDs are far from inert sites of neutral lipid storage; rather, they represent key organelles that play vital roles in the metabolic state of the cell. In this review, we will examine the biology of these structures and outline recent efforts being made to understand the effects of alcohol exposure on the biogenesis, catabolism, and motility of LDs and how their dynamic nature is perturbed in the context of ALD.